Analyzing Question Intonation On Speaking Production Of Students TBI-A Fifth Semester through PRAAT System at IAIN Madura - Sukron Makmun; Nazilatul Wahyuni (Journal of Mandalika Literature, 2025)
This research is about question intonation error on speaking production happened in the class of university, the researcher collecting data at TBI-A class fifth semester at IAIN Madura. To know the high or low the pitch in question intonation from students, it must be analyzed by using praat system, where the praat system itself is a system for analyzing sounds or phonetics. This program is often used to analyze sounds with a variety of language, both regional and international language. praat system can be also use for native speaker and also non native speaker. Through this program, the PRAAT system can produce wave charts that show intonation, intensity, volume and other complex details. The researcher used a qualitative research by descriptive research design to answers the questions. Then, the researcher used interview, observation and documentation to get the data. This research is done by process of analyzing data then making conclusion of the research.